British Women Writing Fiction - Werlock, Abby H. P. (Book collections on Project MUSE., 2000)
"British women in the second half of the 20th century have produced a body of work that is as diverse as it is entertaining. This book offers an informal, jargon-free introduction to the fiction of sixteen contemporary writers either brought up or now living in England. Book jacket."--Jacket